A RARE CASE OF CONJOINED TWIN MONSTER (ISCHIOPAGUS) IN A SHE BUFFALO - SIMON, M SHIJU; WILLIAM, B JUSTIN; Kannan, T A (The Indian Journal of Animal Reproduction, 2023)
A case report of conjoined twin monster in a she buffalo was presented.